Mariusz Rosik, Kodeks Synajski. Biografia (Wrocław: Chronicon 2015) - Bąk, Tomasz (Verbum Vitae, 2016)
Recenzja książki: Mariusz Rosik, Kodeks Synajski. Biografia (Wrocław: Chronicon 2015). Ss. 136. PLN 29. ISBN 978-83-942734-1-5.